2017
DOI: 10.1515/botcro-2016-0052
|View full text |Cite
|
Sign up to set email alerts
|

A morphological study on the dioecious endemic Erodium somanum H. Peşmen (Geraniaceae), critically endangered in Turkey

Abstract: -Morphological features of the endemic Erodium somanum are investigated based on the specimens collected from natural populations from Soma in Manisa. Almost all morphological characteristics are expanded and some morphological characteristics are fi rstly determined in this study. E. somanum is a dioecious species and in this study drawings of male and female individuals are given for the fi rst time. An umbel is 3-5 fl owered in female plants and 6-11 fl owered in male plants, pedicels accrescent to 20-25 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Investigation of published materials on seed morphology has shown that representatives of Pelargonium, Geranium and Erodium (Geraniaceae) genera differ in size, shape and surface topology of mericarps, while seeds of such species as Geranium purpureum, G. pyrenaicum, G. robertianum and E. somanum are similar in shape, but very different in surface topology and colouration (Oskay, 2017;Deniz et al, 2018). Unlike germinants of the Geranium genus, which have a large curved embryo, those of P. sidoides have a smaller spade-shaped embryo (Sravnitel'naya…, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of published materials on seed morphology has shown that representatives of Pelargonium, Geranium and Erodium (Geraniaceae) genera differ in size, shape and surface topology of mericarps, while seeds of such species as Geranium purpureum, G. pyrenaicum, G. robertianum and E. somanum are similar in shape, but very different in surface topology and colouration (Oskay, 2017;Deniz et al, 2018). Unlike germinants of the Geranium genus, which have a large curved embryo, those of P. sidoides have a smaller spade-shaped embryo (Sravnitel'naya…, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Seed characteristics and microsculpturing of E. pelargoniiflorum are given in this study and this is the second documentation about seed microsculpturing in Erodium. The other study is morphological study about dioecious endemic Erodium somanum H. Peşmen [4]. When looking at the each species, in terms of seed micromorphology, it said that both species show similar properties.…”
Section: Mericarp Morphology and Micromorphology Have An Important Plmentioning
confidence: 99%
“…Erodium L'Herit is represented many species on all continents except Antarctica and the Mediterranean region is the largest center of diversity of the genus [1]. This region has 63 species (74 taxa) according to Fiz et al [1] while has much more species up to 87 for now, with taxa in Turkey, according to Davis [2,3], Oskay [4]. The genus Erodium shows distribution a total of 30 taxa with 25 species and subspecies in Turkey, and 16 of these taxa are endemic [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Naggar (2008) investigated seed morphology and seed coat sculpture of 14 native species of Erodium in Egypt and he emphasised that size, shape, epidermal cell patterns of seeds were important for taxonomic of Erodium species. Recently, several studies about morphology, autecology, conservation biology, caryology, fruit, seed and pollen micromorphology of E. somanum and E. pelargoniiflorum carried out by Oskay (2010;2017), Oskay et al (2011;2018). Ather et al (2012) prepared palynology atlas of Pakistan and studied pollen morphology of E. cucitarium and E. malacoides species.…”
Section: Introductionmentioning
confidence: 99%